PENCEMARAN LAUT OLEH SENYAWA ORGANOTIN - Agus Sudaryanto (Jurnal Teknologi Lingkungan, 2001)
Organotin compounds have attracted to focusing study due to theirbioaccumulative potential and deleterious effects to the aquatic organisms. These compounds are ubiquitous contaminants in the environment and have been used commercially for many years and in a variety of diverse applications as polyvinyl chloride (PVC) stabilizers, industrial catalysts, wood preservatives and biocides. Direct exposure to organotin into aquatic environments generally through the usage of TBT in antifouling paints applied for boat, marine infrastructures and aquaculture net. Due to its persistency and biological effects at various organisms, many developed countries have banned and restricted the TBT usage for boating and aquaculture purposes. In this paper the aquatic ecotoxicology of organotin based on a multidisciplinary approach is reviewed.